2020
DOI: 10.3389/fsurg.2020.573398
|View full text |Cite
|
Sign up to set email alerts
|

mHealth Apps for Enhanced Management of Spinal Surgery Patients: A Review

Abstract: mHealth (mobile health) refers to mobile technologies that aid medical and public health practices. As of February 2019, 81% of Americans own a smartphone, and mHealth applications (apps) have become increasingly common with more than 400,000 mHealth applications currently available. Advancements in mobile technology now allow us to provide personalized up-to-date information, track personal health data, remind and engage patients, and communicate in a cost-effective way. There are new opportunities for health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
(33 reference statements)
1
15
0
Order By: Relevance
“…A reduction in ER visits at large tertiary medical centers, such as the one where this study was conducted, may help alleviate ER overcrowding and enable more efficient workflows for emergency medicine providers, resulting in tangible benefits for both providers and other patients in need of emergency care. These benefits have been reported in other studies as well, with a systematic review of mobile health technologies for surgical patients reporting that mobile apps have been shown to reduce postoperative emergency visits, prevent inappropriate visits for wound checks, and improve adherence to postoperative rehabilitation [30]. In the realm of spine surgery, one study noted that many in-person follow-ups were avoided with the use of a mobile app, as it allowed issues such as pain control to be resolved remotely [38].…”
Section: Impact On Providerssupporting
confidence: 63%
See 1 more Smart Citation
“…A reduction in ER visits at large tertiary medical centers, such as the one where this study was conducted, may help alleviate ER overcrowding and enable more efficient workflows for emergency medicine providers, resulting in tangible benefits for both providers and other patients in need of emergency care. These benefits have been reported in other studies as well, with a systematic review of mobile health technologies for surgical patients reporting that mobile apps have been shown to reduce postoperative emergency visits, prevent inappropriate visits for wound checks, and improve adherence to postoperative rehabilitation [30]. In the realm of spine surgery, one study noted that many in-person follow-ups were avoided with the use of a mobile app, as it allowed issues such as pain control to be resolved remotely [38].…”
Section: Impact On Providerssupporting
confidence: 63%
“…This is one of the first studies to document tendencies in acute outcomes associated with the use of a mobile health tool for patients undergoing spine surgery. Previously published research on mobile health solutions for spine surgery demonstrated the viability of using apps to engage patients in their recovery process and documented one such app that resulted in decreased pain scores when compared to traditional rehabilitation alone [ 30 ]. However, very few spine surgery apps have been linked with ER visits or complications.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is expanding evidence for the role of mHealth in postoperative monitoring after spine surgery, 17,46,47 and there are increasingly available commercial applications intended to aid post-discharge patient surveillance. [48][49][50] Particularly notable, one study used a mobile 18 & Linkage with EHR/registry data 19 application to aid postoperative monitoring for over 1,600 enhanced recovery after surgery patients. More generally, mHealth used in spine surgery has shown success in collecting patient-reported outcome measures, 51 decreasing surgical cancellations, 52 monitoring postoperative recovery, 17,46 and guiding postoperative rehabilitation.…”
Section: Mobile Datamentioning
confidence: 99%
“…Mobile health (mHealth) services refer to the provision of medical services to users through mobile devices, such as smartphones, tablet computers, and satellite communications ( Jovanov and Zhang, 2004 ; Bai et al, 2020 ; Bally and Cesuroglu, 2020 ; Lee, 2021 ; Sujarwoto et al, 2022 ). mHealth services have changed the traditional healthcare and played an increasing important role in the medical service delivery through their unique features, such as ease of use, usefulness and convenience ( Liu et al, 2019 ; Crowell et al, 2022 ; Zhao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%